Tratamiento de las Cuentas por Pagar del GAD Parroquial Rural de San Juan - Cedeño Luque, Melissa Yasmin (2019)
The Rural Parochial Decentralized Autonomous Government of San Juan de Juana de Oro belonging to the San Francisco Canton of Pueblo Viejo is located 22 km from the provincial capital of Los Ríos. The parish GAD San ​​Juan has an organizational structure of democratic ideal where its highest authority is the president of the parish government, vice president, treasurer - secretary and followed by principal and alternate members respectively. The planning and public finance code in its article 150 establishes that in each entity the administration unit for the execution of the Government Accounting Unit will be established in such a way that it allows it to recognize the budgetary and accounting information separately.